The definitive guide to Drupal 7 - Melançon, Benjamin (Apress, 2011)
Definitive guide to Drupal 7 is the most comprehensive book for getting sites done using the powerful and extensible Drupal content management system. Written by a panel of expert authors, the book covers every aspect of Drupal, from planning a successful project all the way up to making a living from designing Drupal sites and to contributing to the Drupal community yourself. With this book you will: Follow practical approaches to solving many online communication needs with Drupal with real examples. Learn how to keep learning about Drupal: administration, development, theming, design, and architecture. Go beyond the code to engage with the Drupal community as a contributing member and to do Drupal sustainably as a business.